Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 7004 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Mya arenaria Linnaeus, 1758" ] } The dataset includes 7004 records from 147 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0057704-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences